FATWA JIHAD DAN RESOLUSI JIHAD: HISTORISITAS JIHAD DAN NASIONALISME DI INDONESIA - Juma' Juma' (Aqlam: Journal of Islam and Plurality, 2022)
Abstract;The arrival of allies in post-independence Indonesia raised concerns among the founding fathers and kiai of re-colonization. One of the responses to the arrival of the allied troops came from Nahdlatul Ulama (NU), which is known for its jihad fatwas and resolusi jihad. The resolusi jihad became NU's national ijtihad in order to prevent re-colonization in Indonesia (defensive jihad). This call calls on the official government of Indonesia to carry out an armed struggle, as well as calling on all people to jihad fi sabilillah. The resolusi jihad is an anti-colonial nationalism that was born out of a burst of love for an independent Indonesia, the arrival of allies, and the Orange Hotel incident. The spirit of nationalism coupled with the precarious condition of the nation gave birth to the jihad fi sabilillah movement. The principle of love for the motherland and jihad to defend an independent country is fardhu ain, obligatory for every Muslim. This spirit of jihad and nationalism swelled among students and fighters for peace against allies, colonialists, for the sake of upholding the sovereignty of the Republic of Indonesia.Keywords: Resolusi Jihad, nationalisme of jihad, anti-colonialismAbstrak; Kedatangan sekutu di indonesia pasca kemerdekaan memunculkan kekhawatiran di kalangan pendiri bangsa dan kiai akan terjadinya penjajahan kembali. Respon atas kedatangan tentara sekutu salah satunya hadir dari Nahdlatul Ulama (NU), yang dikenal dengan fatwa jihad dan resolusi jihad. Resolusi jihad menjadi ijtihad kebangsaan NU demi menghalau terjadinya penjajahan kembali di Indonesia (jihad defensive). Seruan ini menghimbau pemerintah resmi Indonesia untuk melakukan perjuangan bersenjata, sekaligus menghimbau seluruh rakyat untuk jihad fi sabilillah. Resolusi jihad merupakan nasioanlisme anticolonial yang lahir dari letupan kecintaan terhadap Indonesia merdeka, kedatangan sekutu, dan insinden hotel oranje. Semangat nasionalisme yang dibarengi dengan kondisi bangsa yang genting melahirkan gerakan jijhad fi sabilillah. Prinsip cinta tanah air dan jihad membela negara merdeka menjadi fardhu ain, wajib bagi setiap muslim. Semangat jihad dan nasionalisme ini menggelembung di kalangan santri dan pejuang untuk berperangan melawan sekutu, pejajah, demi tegaknya kedaulatan negara republik Indonesia.Keywords: Resolusi Jihad, Jiihad Nasionalisme, anti-kolonialisme